Dari Piksel ke Paragraf: Pemetaan Kesalahan Penulisan Kalimat Efektif dalam Teks Berita Siswa XI DKV - Salsabila Khoerunnisa; Lalita Melasarianti; Vera Krisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the linguistic competence gap observed in vocational high school (SMK) students majoring in Visual Communication Design (DKV), where dominant visual communication skills are often not matched by adequate verbal-written proficiency. The core issue addressed is the low mastery of effective sentence rules in composing news texts, which demand high objectivity and precise information. This study aims to identify, analyze, and comprehensively map the forms of effective sentence writing errors in news texts produced by eleventh-grade DKV students at SMK Kesatrian Purwokerto. Using a qualitative descriptive approach, the study identifies linguistic lapses based on the framework of Alwi et al. (2017). Data were collected through a news-writing performance test. The results reveal a total of 430 errors classified into five major categories. The most dominant error is